Factors that determine the provision of Public Service Interpreting: comparative perspectives on government motivation and language service implementation - Ozolins, Uldis (The Journal of Specialised Translation, 2010)
This paper undertakes a comparative examination of language service policy, as various countries struggle to meet multilingual communication needs. Four macro factors are posited that affect provision of public service interpreting:Increasing linguistic diversityReliance on public sector financeInstitution-led, rather than profession-led standards and practicesCross-sectoral interpreting needs that conflict with usual sector-specific policy developmentWhile these factors affect policy in all countries, it is argued that countries differ widely in other crucial aspects that affect language service policy, including overall attitudes to immigrants; divergent models of government service provision; federalism or unitarianism in government; whether legal/court interpreting is favoured over other sectors; and even variation in response to the very concept of 'interpreting.' Examination of these factors allows us to understand differences in such outcomes as provision of interpreter training, certification, allocation of resources and reach of language services.Specific motivations for government interpreting policy are examined to see how governments can be persuaded to take initiatives to develop language services, looking at normative factors, building of coalitions to press for services, and attending to the interactions between such factors as training, certification and finance to ensure quality language services.